PERFORMATIVITAS DALAM NOVEL THE FEMALE MAN KARYA JOANNA RUSS - , wilujeng asih purwani; , Dr. Wening Udasmoro, M. Hum., DEA., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis examines identity building of lesbian women through their act of performativity. Performativity is commonly understood as the declarations that create new facts. Women are transformed into object of tradition in order to produced the patriarchal social order and produce gender identity. Science fictionâs possibility exists because of its novelty in conceptual exploration of âa new worldâ. Joanna Russ made an argument that the forms of symbolic contingency found in the genre provided a productive space for the critique of patriarchal heterosexuality. Joanna Russ' essays written around the period of production and publication of The Female Man show a preoccupation with generic structure of science fiction. Russ wrote essays that explored the radical possibilities that existed in the genre, along with the very real limitations in its execution. The Female Man show how the utopian world comes in to the world of lesbian. By utopia future, people create a reformulation of law for their life. This law makes possibility to change the patriarchal world become more acceptable. By the theory of Judith Butler, the writer of this thesis will apply to Joanna Russ' the female man. This thesis described that Joanna escapes from the hegemony of American Society concerned with her gender identity because she wants her lesbian identity being recognized. In order to earn acknowledgment about her lesbian identity Joanna Russ indicates performativity repeatedly. Joanna represented utopia and lesbian community aims to create her identity existence.